Combining 1H-NMR-based metabonomics and network pharmacology to dissect the mechanism of antidepression effect of Milletia speciosa Champ on mouse with chronic unpredictable mild stress-induced depression. (9th April 2021) - Su, Zhiheng; Ruan, Junxiang; Liu, Xi; Zheng, Hua; Ruan, Jingzhou; Lu, Yuying; Cheng, Bang; Wu, Fang; Wu, Jinxia; Liu, Xuwen; Song, Fangming; Chen, Zhaoni; et al.
Abstract: Objectives: Milletia speciosa Champ (MS), a traditional Chinese medicine, has the abilities of antistress, antifatigue, anti-oxidation and so on. In our previous study, MS was found to antidepression while the underlying mechanism of which needs further elucidation. Methods: Here, a proton nuclear magnetic resonance ( 1 H-NMR)-based metabonomics combined network pharmacology research approach was performed to investigate the antidepressive mechanism of MS act on mouse with chronic unpredictable mild stress-induced depression. Key findings: Results showed that MS could alleviate the ethology of depression (including sucrose preference degree, crossing lattice numbers and stand-up times) and disordered biochemical parameters (5-hydroxytryptamine, norepinephrine and brain-derived neurotrophic factor). Metabonomics study and network pharmacology analysis showed that MS might improve depression through synergistically regulating five targets including Maoa, Maob, Ache, Ido1 and Comt, and three metabolic pathways such as tryptophan metabolism, synthesis of neurotransmitter and phospholipid metabolism. Conclusions: This study for the first time preliminary clarified the potential antidepressive mechanism of MS and provided theoretical basis for developing MS into novel effective antidepressant.